MONEY SUPPLY, COUNTERFEIT MONEY, AND ECONOMIC GROWTH EFFECT TO E-MONEY TRANSACTION - Putri, Chintia Ariani; Prasetyo, P. Eko (Universitas Negeri Semarang, 2020)
Electronic money is an innovation in payment systems. Although transactions continue to increase, the ratio of electronic money transactions to transactions using the Card Payment Instrument is always less than 1%. The purpose of this study is to determine the effect of monetary instruments namely the money supply (M1), counterfeit money, and economic growth on electronic money transactions in Indonesia. This research uses a quantitative method using time series data during the period January 2016 - December 2018. Data analysis uses multiple linear regression with a double log model based on OLS. The results of this study indicate that the money supply (M1) has a positive and significant effect on electronic money transactions, counterfeit money has no significant effect on electronic money transactions, economic growth has a positive and significant effect on electronic money transactions. The implication of this research is that electronic money should be given additional security such as PIN so that when the owner loses it will not lose the balance contained therein, Bank Indonesia should encourage and encourage the public to switch to using electronic money so that it can reduce the money supply and avoid the risk of counterfeit money.  Uang elektronik merupakan inovasi dalam sistem pembayaran. Meskipun transaksi terus meningkat, rasio transaksi uang elektronik dengan transaksi menggunakan Instrumen Pembayaran Kartu selalu kurang dari 1%. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh instrumen moneter yaitu jumlah uang beredar (M1), uang palsu, dan pertumbuhan ekonomi pada transaksi uang elektronik di Indonesia. Penelitian ini menggunakan metode kuantitatif menggunakan data deret waktu selama periode Januari 2016 - Desember 2018. Analisis data menggunakan regresi linier berganda dengan model log ganda berdasarkan OLS. Hasil penelitian ini menunjukkan bahwa jumlah uang beredar (M1) berpengaruh positif dan signifikan terhadap transaksi uang elektronik, uang palsu tidak berpengaruh signifikan terhadap transaksi uang elektronik, pertumbuhan ekonomi berpengaruh positif dan signifikan terhadap transaksi uang elektronik. Implikasi dari penelitian ini adalah bahwa uang elektronik harus diberikan keamanan tambahan seperti PIN sehingga ketika pemilik kehilangan itu tidak akan kehilangan saldo yang terkandung di dalamnya, Bank Indonesia harus mendorong dan mendorong masyarakat untuk beralih menggunakan uang elektronik sehingga dapat mengurangi jumlah uang beredar dan menghindari risiko uang palsu.